Food insecurity among people who inject drugs in Los Angeles and San Francisco. Issue 12 (9th March 2016) - Schmitz, Jane; Kral, Alex H; Chu, Daniel; Wenger, Lynn D; Bluthenthal, Ricky N
Abstract: Objective: We estimated the prevalence of food insecurity among people who inject drugs (PWID) in Los Angeles and San Francisco and explored correlates of food insecurity. Design: A cross-sectional study that measured 30 d food insecurity using the US Adult Food Security Survey ten-item Module developed by the US Department of Agriculture. Food insecurity was defined as including low and very low food security. Setting: Two cities in the state of California, USA. Subjects: Male and female active PWID ( n 777). Results: Among participants, 58 % reported food insecurity and 41 % reported very low food security. Food-insecure PWID were more likely to report being homeless (prevalence ratio (PR)=1·20; 95 % CI 1·05, 1·37), chest pain in the past 12 months (PR=1·19; CI 1·06, 1·35), acquiring syringes from someone who goes to a syringe exchange programme (PR=1·27; 95 % CI 1·13, 1·43) and feeling at risk for arrest for possession of drug paraphernalia (PR=1·30; 95 % CI 1·15, 1·46). Conclusions: Current food insecurity was common among PWID in these two cities, yet few factors were independently associated with food insecurity. These data suggest that broad strategies to improve food access for this high-risk population are urgently needed.